Multiple factors govern the biogeographic distribution of archaeal community in mangroves across China. (31st December 2019) - Li, Ruili; Tong, Tianli; Wu, Sijie; Chai, Minwei; Xie, Shuguang
Abstract: Archaea can participate in the biogeochemical processes in mangrove ecosystem. The biogeographic distribution of archaeal community in mangroves remains poorly known. In this study, six mangroves at different geographic locations in China were selected. Mangrove archaeal community was found to considerably change with geographic location, which might be driven by a variety of environmental variables (etc., pH and carbon and nitrogen contents). Archaeal communities were primarily comprised of Thaumarchaeota (54.7–85.2%) and Euryarchaeota (11.8–43.9%). This work could provide some new insights towards the distribution of archaeal community in mangrove ecosystem.